Altered patterns of gene expression underlying the enhanced immunogenicity of radiation-attenuated schistosomes. - Gary P Dillon; Theresa Feltwell; Jason Skelton; Patricia S Coulson; R Alan Wilson; Alasdair C Ivens (PLoS Neglected Tropical Diseases, 2008)
Schistosome cercariae only elicit high levels of protective immunity against a challenge infection if they are optimally attenuated by exposure to ionising radiation that truncates their migration in the lungs. However, the underlying molecular mechanisms responsible for the altered phenotype of the irradiated parasite that primes for protection have yet to be identified.We have used a custom microarray comprising probes derived from lung-stage parasites to compare patterns of gene expression in schistosomula derived from normal and irradiated cercariae. These were transformed in vitro and cultured for four, seven, and ten days to correspond in development to the priming parasites, before RNA extraction. At these late times after the radiation insult, transcript suppression was the principal feature of the irradiated larvae. Individual gene analysis revealed that only seven were significantly down-regulated in the irradiated versus normal larvae at the three time-points; notably, four of the protein products are present in the tegument or associated with its membranes, perhaps indicating a perturbed function. Grouping of transcripts using Gene Ontology (GO) and subsequent Gene Set Enrichment Analysis (GSEA) proved more informative in teasing out subtle differences. Deficiencies in signalling pathways involving G-protein-coupled receptors suggest the parasite is less able to sense its environment. Reduction of cytoskeleton transcripts could indicate compromised structure which, coupled with a paucity of neuroreceptor transcripts, may mean the parasite is also unable to respond correctly to external stimuli.The transcriptional differences observed are concordant with the known extended transit of attenuated parasites through skin-draining lymph nodes and the lungs: prolonged priming of the immune system by the parasite, rather than over-expression of novel antigens, could thus explain the efficacy of the irradiated vaccine.